Classes involved in implementing remote method invocation (RMI) feature in java - Sudarsan, V; Sugumar, R (International Journal of Engineering and Technology, 2018)
This work is aimed at discussing about the Java classes that are involved in implementing the Remote Method Invocation feature in Java. Remote Method Invocation feature is used in applications involving distributed processing. Applications based on distributed processing enable load sharing.
Keywords: Java Classes Involved in Implementing RMI; Remote Method Invocation; RMI in Java